Effects of Colostrum Probiotics on ACE-2 Expression and Hematology in Murine Models Immunized Against Canine Coronavirus - Hamid, Iwan Sahrial; Solfaine, Rondius; Supriyadi, Supriyadi (Universitas Airlangga, 2025)
In modern society, the human-animal bond has significantly strengthened, with pets evolving into integral family members providing psychological support to their owners. In the current landscape of heightened focus on immune health and the widespread utilization of probiotic advancements globally, this study investigates the potential of colostrum probiotics to influence hematological profiles and ACE-2 expression in a murine model of canine coronavirus (CCV) infection. Twenty-four mice were categorized into four treatment groups: (C) placebo, (T1) CCV induction + isoprinosine, (T2) CCV induction + probiotic-based, and (T3) CCV induction + colostrum-based probiotics. CCV induction was performed via subcutaneous injection of a live-attenuated CCV vaccine at 60 mg/kg body weight for 7 consecutive days. Probiotics were administered via oral gavage for 14 consecutive days. On the 15th day post-treatment, euthanasia was performed, and blood samples were collected to examine hematological profiles and ACE-2 enzymes in the intestinal tissue sections. Data analysis, conducted using ANOVA followed by Duncan's test (p < 0.05), revealed a significant improvement in the T3 group, particularly in leukocytes, hemoglobin, lymphocytes, neutrophils, and ACE-2 expression. In conclusion, this study suggests that probiotics, specifically colostrum-based, enhance immune parameters and ACE-2 expression in the intestinal milieu of murine model subjected to CCV immunization.